2019
DOI: 10.1111/tbed.13297
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebrospinal fluid analyses of severe pseudorabies encephalitis

Abstract: We reported a severe human pseudorabies encephalitis case and described a dynamic clinical manifestation with cerebrospinal fluid analyses and cytological and serological evaluation, which may elucidate the mechanism of PRV infection and facilitate clinical diagnosis and treatment in human.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Studies about piscidin 1 and resveratrol have provided some alternative measures for SHV1 infection, but clinical trials need to be carried out in the future [19,20] . Intriguingly, some SHV1 encephalitis patient showed an improvement of consciousness after immediate administration of both penciclovir or ganciclovir plus foscarnet sodium treatment [2,9] . The prompt antiviral treatment might attenuate severe SHV1 encephalitis and facilitate the clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies about piscidin 1 and resveratrol have provided some alternative measures for SHV1 infection, but clinical trials need to be carried out in the future [19,20] . Intriguingly, some SHV1 encephalitis patient showed an improvement of consciousness after immediate administration of both penciclovir or ganciclovir plus foscarnet sodium treatment [2,9] . The prompt antiviral treatment might attenuate severe SHV1 encephalitis and facilitate the clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…All patients came from Mainland China, including 8 cases from Shandong province, 2 cases from Inner Mongolia, 2 cases from Henan province, 2 cases from Hebei province, one case from Hubei province, one case from Guangdong province, one case from Anhui province, and one case from Beijing. Therefore, a total of 20 cases (male: 17; female: 3) of human SHV1 encephalitis were included in the summarization (Table 1 and Supplemental Table 1 Yang et al [5] 43 Zheng et al [9] 59/M Swineherd fever, seizures, disturbed consciousness, respiratory failure, eye involvement positive 8/ND positive ganciclovir and foscarnet, antiepileptic, antibiotics loss mRS 14 Wang et al [10] 44/M Pork vendor fever, seizures negative 74/ND positive full-dose acyclovir, antiepileptic, antibiotics, GC follo instr mRS 15 Yang et al [11] 50…”
Section: Clinical Features and Treatment Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…In the performed infection assays, HEK293T cells were employed to investigate the effects of BAG3 overexpression or knockdown on lytic infection of PRV. We used HEK293T cells because: (i) Human cell lines are susceptible to PRV, and support the efficient replication of PRV [35,36], (ii) HEK293T cells are highly efficient for overexpression of foreign protein by the transfected plasmid, and (iii) PRV has been reported in several recent case reports to infect humans, which results in encephalitis [37][38][39][40][41][42]. Both overexpression and knockdown assays indicated that BAG3 played a negative regulation role during PRV lytic infection.…”
Section: Discussionmentioning
confidence: 99%